2016
DOI: 10.1007/s11249-016-0708-5
|View full text |Cite|
|
Sign up to set email alerts
|

Friction-Induced Transformation from Graphite Dispersed in Esterified Bio-Oil to Graphene

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
(50 reference statements)
1
14
0
Order By: Relevance
“…Persson [12] said that the mix of particles with water is highly viscous and then lubricates more the tire/road interface. The lubricating action of particles mixed with lubricants has been observed in other tribosystems like piston ring-cylinder liner pairs in internal combustion engines [13][14] [15]. These authors have shown that adding additives like molybdenum disulfide [13] [14] or graphite [15] in oils helps to reduce friction and wear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Persson [12] said that the mix of particles with water is highly viscous and then lubricates more the tire/road interface. The lubricating action of particles mixed with lubricants has been observed in other tribosystems like piston ring-cylinder liner pairs in internal combustion engines [13][14] [15]. These authors have shown that adding additives like molybdenum disulfide [13] [14] or graphite [15] in oils helps to reduce friction and wear.…”
Section: Introductionmentioning
confidence: 99%
“…The lubricating action of particles mixed with lubricants has been observed in other tribosystems like piston ring-cylinder liner pairs in internal combustion engines [13][14] [15]. These authors have shown that adding additives like molybdenum disulfide [13] [14] or graphite [15] in oils helps to reduce friction and wear. Xu and coauthors in [15] attributed this performance to the higher viscosity of oil with additives (an esterified bio-oil has been used) compared with pure oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in order to improve the yield of production of single layer graphene, Xu et al [72] used a friction-induced exfoliation from graphite to graphene in esterified bio-oil. They dispersed flake graphite into the esterified bio-oil and then measured the tribological response of the dispersed graphene after ultrasonication for 20 min.…”
Section: Modified Mechanical Exfoliationmentioning
confidence: 99%
“…In order to better understand the tribological properties of α-ZrP, we selected MoS 2 and graphite as the reference in this research. Because MoS 2 and graphite are the conventional solid lubricant, which are usually used as additives in calcium grease [16][17][18][19]. The tribological performance of α-ZrP, MoS 2 , and graphite anhydrous calcium grease was evaluated at different applied loads, frequencies, temperatures, and durations.…”
Section: Introductionmentioning
confidence: 99%